Solution to Economic Load Dispatch using Particle Swarm Optimization - Onundo, Patricia Lucy; Abungu, N.O (My University, 2014)
This paper proposes to determine the feasible optimal solution of the economic load dispatch power systems problem using Particle Swarm Optimization (PSO) considering various generator constraints. The objective of the proposed method is to determine the steady-state operating point which minimizes the fuel cost, while maintaining an acceptable system performance in terms of limits on generator power, line ﬂow, prohibited operating zone and non linear cost function. Three diﬀerent inertia weights; a constant inertia weight CIW, a timevarying inertia weight TVIW, and global-local best inertia weight GLbestIW, are considered with the (PSO) algorithm to analyze the impact of inertia weight on the performance of PSO algorithm. The PSO algorithm is simulated for each of the method individually. It is observed that the PSO algorithm with the proposed inertia weight (GLbestIW) yields better results, both in terms of optimal solution and faster convergence.
Keywords: Classical particle swarm optimization (CPSO; Economic load dispatch